Placenta‐mediated complications: Nucleosomes and free DNA concentrations differ depending on subtypes. (18th October 2020) - Bouvier, Sylvie; Mousty, Eve; Fortier, Mathieu; Demattei, Christophe; Mercier, Eric; Nouvellon, Eva; Chea, Mathias; Grosjean, Frédéric; Letouzey, Vincent; Gris, Jean‐Christophe
Abstract: Background: Placenta‐mediated pregnancy complications generate short‐ and long‐term adverse medical outcomes for both the mother and the fetus. Nucleosomes and free DNA (fDNA) have been described in patients suffering from a wide range of inflammatory conditions. Objective: The objective of our study was to compare nucleosomes and fDNA circulating levels during pregnancy and particularly in women developing a placenta‐mediated complication according to the subtype (preeclampsia or intrauterine growth restriction) (NCT 01736826). Patients/Methods: A total of 115 women were prospectively included in the study across three groups: 30 healthy non‐pregnant women, 50 with normal pregnancy, and 35 with a complicated pregnancy. Blood samples were taken up to every 4 weeks for several women with normal pregnancy and nucleosomes and fDNA were quantified using enzyme‐linked immunosorbent assay and quantitative polymerase chain reaction, respectively. Results: We show that nucleosomes and fDNA concentrations significantly increase during normal pregnancy, with concentrations at delivery differing between the two groups. Interestingly, we show that concentrations differ according to the type of placenta‐mediated complications, with higher levels in preeclampsia compared to intrauterine growth restriction. Conclusions: These data suggest that nucleosomes and fDNA may be additional actors participating in placenta‐mediated pregnancy complications.